PERISTILAHAN AKTIVITAS MASYARAKAT DI KAWASAN ALIRAN SUNGAI SAMBAS - Yustin Savitri; Patriantoro Patriantoro; Amriani Amir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was motivated by activities carried out by the community in the Sambas river flow, such as household activities, as transportation routes, sources of livelihoods, and entertaiment facilities. A common problem in this research was the Terminology of Community Activities in the Sambas River Flow.Common problems are divided into three subproblems, namely the terminologyform, lexical meanings and cultural meanings, and components of meaning. This research was conducted using descriptive methods with qualitative forms. The method of data collection used were observation, interviews, and documentation.This research was successful collecting 43 terminology data. From the 43 terminologies of the activity, 35 terminologieswere in the form  of word, and 8 terminologieswere in the form of phrases.The 43 terminologieswere grouped into 4 types of activities, namely households, transportation routes, sources of livelihood, and entertaiment facilities.Cultural meanings are divided into 1 myth in the activity category and 3 forbidden in the tool dan activities category. Based on the analysis of meaning components there were 21 terminology datas. Keywords:Terminology,Activity,Lexical Meaning, Cultural Meaning